2020
DOI: 10.47162/rjme.61.2.08
|View full text |Cite
|
Sign up to set email alerts
|

Tumor recurrence in parasagittal and falcine atypical meningiomas invading the superior sagittal sinus

Abstract: This is an open-access article distributed under the terms of a Creative Commons Attribution-NonCommercial-ShareAlike 4.0 International Public License, which permits unrestricted use, adaptation, distribution and reproduction in any medium, non-commercially, provided the new creations are licensed under identical terms as the original work and the original work is properly cited. ORIGINAL PAPER Tumor recurrence in parasagittal and falcine atypical meningiomas invading the superior sagittal sinus ANDREI IONUŢ C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 91 publications
3
11
0
1
Order By: Relevance
“…Meanwhile, postoperative PTE fadeaway within 3 months after operation demonstrated complex and different mechanisms of preoperative PTE such as venous compression, expression of VEGF or rich blood supply and a lower rate of tumor cell invading brain tissue. We also found tumor located in superior sagittal sinus were one of the risk factors associated with tumor recurrence which is similar to previous research [31][32][33]. In this region in which venous lakes and large con uent veins are commonly found, which means tumor with superior sagittal sinus invasion may compress the vein causing PTE.…”
Section: Discussionsupporting
confidence: 90%
“…Meanwhile, postoperative PTE fadeaway within 3 months after operation demonstrated complex and different mechanisms of preoperative PTE such as venous compression, expression of VEGF or rich blood supply and a lower rate of tumor cell invading brain tissue. We also found tumor located in superior sagittal sinus were one of the risk factors associated with tumor recurrence which is similar to previous research [31][32][33]. In this region in which venous lakes and large con uent veins are commonly found, which means tumor with superior sagittal sinus invasion may compress the vein causing PTE.…”
Section: Discussionsupporting
confidence: 90%
“…As reported by Mantovani and Mohammed et al., the parasagittal meningioma subgroup accounts for 19.5%–45% of all intracranial meningiomas 24,25 . Further, parasagittal and falcine meningiomas are the second most frequently occurring intracranial meningiomas 6 …”
Section: Discussionmentioning
confidence: 86%
“…24,25 falcine meningiomas are the second most frequently occurring intracranial meningiomas. 6 Some studies have reported prediction of grading, differential diagnosis, and prognosis of meningiomas using radiomic signatures (e.g., T1C, T2, DWI, T1WI, T1C, and ADC mapping). 8,[26][27][28] Hence, we explored the radiomic signatures associated with meningioma sinus invasion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although maximal resection of the adjacent bone is preferred [ 37 ], this can be challenging due to anatomical circumstances, such as extensive involvement of the skull base, infiltration of dural sinuses, or envelopment of arteries, cranial nerves, or muscle [ 38 , 39 , 40 , 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%